2021
DOI: 10.3390/ma14061575
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Nitrogen Doped Titanium Dioxide Surface Layer on NiTi Shape Memory Alloy

Abstract: NiTi shape memory alloys are increasingly being used as bone and cardiac implants. The oxide layer of nanometric thickness spontaneously formed on their surface does not sufficiently protect from nickel transition into surrounding tissues, and its presence, even in a small amount, can be harmful to the human organism. In order to limit this disadvantageous phenomenon, there are several surface engineering techniques used, including oxidation methods. Due to the usually complex shapes of implants, one of the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The findings indicate that, when compared to oxygen-based plasma, cathodic sputtering in an argon-nitrogen plasma considerably enhances the thickness of the nitrogen-doped titanium dioxide layer, thereby enhancing the surface properties of NiTi implants. Furthermore, (TiOxNy) 2 diffusion surface layer demonstrates exceptional resistance to E. coli colonization ( Tarnowski et al, 2021 ).…”
Section: Enhancing Impact Of Surface Alteration Of Ni-ti Implant On O...mentioning
confidence: 99%
“…The findings indicate that, when compared to oxygen-based plasma, cathodic sputtering in an argon-nitrogen plasma considerably enhances the thickness of the nitrogen-doped titanium dioxide layer, thereby enhancing the surface properties of NiTi implants. Furthermore, (TiOxNy) 2 diffusion surface layer demonstrates exceptional resistance to E. coli colonization ( Tarnowski et al, 2021 ).…”
Section: Enhancing Impact Of Surface Alteration Of Ni-ti Implant On O...mentioning
confidence: 99%
“…In these studies, TiN, , TiO 2 , , Ti, , and hydroxyapatite coatings have been applied for this purpose using different methods. TiN differs from the others in terms of better mechanical properties and biocompatibility; a passive TiO 2 film is formed during its formation. , In a review study, del Castillo et al, investigating TiN coating specific to dental implants, reported that TiN coatings reduce early bacterial colonization and biofilm formation and improve fibroblast cell attachment and adhesion . In addition, Ag–SiO 2 chemically produced by electrophoretic deposition (EPD) method is used in nanocomposite coatings. Corrosion tests in Ringer’s solution are used to determine the effectiveness of the coatings. , …”
Section: Introductionmentioning
confidence: 99%
“…NiTi shape memory alloys used to make long-term implants, such as stents, must be able to limit nickel ion release into the surrounding biological environment (metallosis). Such properties are ensured to varying degrees by the surface layers produced on the NiTi alloy, such as: titanium oxides, in particular rutile-TiO 2 , titanium nitride-TiN, silicon oxide-SiO 2 , amorphous hydrogenated carbon doped with nitrogen-a-C:N:H, amorphous hydrogenated silicon carbide-a-SiC:N:H produced via different surface engineering methods, which are often applied on, e.g., stents [10][11][12][13][14][15]. A prospective material solution for the shape memory NiTi alloy in terms of its application for cardiological implants is the deposition of composite layers consisting of an interlayer of titanium oxide-TiO 2 -rutile, produced by oxidation under glow-discharge conditions, and a thin a-C:N:H external coating produced via RFCVD.…”
Section: Introductionmentioning
confidence: 99%